Particle disease. A comprehensive theory of periprosthetic osteolysis: a review. - Gallo, Jiri; Kaminek, Petr; Ticha, Vlastislava; Rihakova, Petra; Ditmar, Rudolf (Biomedical papers, 2002)
Aseptic loosening and osteolysis are considered the main long-term problems of hip arthroplasty. Pathogenesis of periprosthetic osteolysis is multifactorial, and both the biological and mechanical factors seem to play an important role. Bearing surfaces continuously generate excessive amounts of micron and submicron particles provoking an adverse inflammatory response of periprosthetic connective tissues. In general, a key role has been attributed to macrophages. Cytokines, growth factors, PGE2, and enzymes are secreted with activated periprosthetic cells resulting in formation of osteolytic granulomas. The final osteolytic step is taken predominantly by osteoclasts which are getting ready for action mainly by an osteoprotegerin ligand (RANKL) and TNFα. Rankl is expressed by activated macrophages, osteoblasts, and lymphocytes. In parallel, a repetitive hydraulic effect of the joint fluid is manifested on the susceptible bone.
Keywords: Arthroplasty / Complications / Pathogenesis / Periprosthetic osteolysis / Particle disease